An integrated solution for the aircraft taxi and gate assignment problems. Issue 1 (1st January 2017) - Behrends, John; Usher, John M.
Abstract: Airlines incur a number of costs associated with moving freight or passengers for one point to another. To manage and control these costs, airlines are constantly looking for areas or opportunities to manage costs and increase efficiency. Various areas or segments of operations have been investigated with little review of the impact of the researched area on other segments of the operation. This research presents a framework for assigning flights to a departure gate that minimizes delays caused by moving passengers or freight to the departing flight and delays incurred during the taxing from the gate to the runway. As part of this research, variations due to travel speed are investigated. In addition to problem formulation, this research presents a solution algorithm incorporating a genetic algorithm that determines the gate assignment scheme resulting in the minimum delay minutes for a given schedule.